COGNITIVE THERAPY UNTUK MENGURANGI PEMIKIRAN NEGATIF - aisyah putri rawe mahardika (JURNAL PSIMAWA, 2023)
Cognitive distortions are irrational or excessive thoughts that are believed to be true, characterized by persistent, persistent negative thoughts. This research aims to reduce the negative thoughts you have. The subject of this research consisted of a woman who had excessive negative thoughts, especially towards men. Subjects think that all men are liars, cannot be trusted and that male friend approach because they want something. The research methods used were observation interviews and psychological tests. The intervention used is cognitive therapy which is structured in five intervention sessions. The aim of the intervention is to reduce negative thinking in the subject. The results of cognitive therapy intervention on the subject show that cognitive therapy provides effective results in reducing negative thoughts by changing them into more positive thoughts.